Synthesis of N-(Hetero)arylconvolvine Derivatives through a Palladium-Catalyzed Buchwald–Hartwig Cross-Coupling - Hassine, Manel; Jannet, Hichem Ben; Ghermani, NourEddine; Alami, Mouad; Messaoudi, Samir (Synthesis, 2020)
The present study describes the isolation of convolvine from the roots of the Tunisian plant Convolvulus dorycnium L. and its synthesis through a four-step sequence starting from tropine. Then, an efficient synthesis of N-(het)aryltropanes derivatives by a sequence of a palladium-catalyzed N-arylationof convolvine has been established. This strategy enabled access to unknown tropane scaffolds of biological interests.
Keywords: convolvine; Buchwald–Hartwig reaction; palladium catalysis; tropane